Revisiting Pre-Service Education for Secondary EFL Teachers in Indonesia (Universitas Negeri Semarang, 2023)
In recent decades, English has gained prominence in Indonesia. However, due to instructors' lack of English proficiency, English instruction at the secondary level shows a significant failure. Today, amid the COVID-19 epidemic, which has pushed remote education, the challenge of teaching English as a foreign language in Indonesian secondary schools becomes more severe. Due to in-service teachers' lack of English proficiency and ICT abilities, future Indonesian English teachers' pre-service education at the secondary level should be revisited. This qualitative study investigates the extent to which teacher education programs (PPG) equip prospective EFL instructors to use Technology, Pedagogy, and Content Knowledge (TPACK) in their classroom instruction. It also explores the viewpoints of pre-service EFL teachers (student teachers) and teacher educators on EFL pre-service teacher education programs at several Teacher Education Institutions (TEIs) in West Java, Indonesia. Results of surveys and semi-structured interviews as the primary data sources underline the importance of preparing future English teachers by utilising TPACK and providing teacher educators with all the skills and materials required to train their students properly. A key finding of this study is the insufficient English competencies of teacher educators and pre-service teachers. This research is vital for improving English teacher education in Indonesia.